40Ar/39Ar dating of the Jurassic volcanic province of Patagonia : migrating magmatism related to Gondwana break-up and subduction - Féraud, G.; Alric, V.; /Fornari, Michel; Bertrand, H.; Haller, M. (1999)
The Mesozoic large igneous province (LIP) of Patagonia (southern South America), which is one of the largest silicic provinces on Earth has been investigated by the 40Ar/39Ar method. Twenty-seven ages considered as valid, including twenty plateau ages, show that the volcanic activity, ranging from 187 to 144 Ma, occurred between and contemporaneously with the initial break-up of Gondwana (starting with the Karoo-Antarctic-Tasmanian (KAT) flood basalt province) in the east, and a subduction in the west. The data display a regular decreasing of ages from the ENE (187 Ma) to the WSW (144 Ma) along about the 650 km, apparently related to the tectonic structure in half-grabens oriented NNW-SSE. The good fitting of this trend with the opening of the Rocas Verdes-Sarmiento marginal basin favors a space-time evolution of this continental volcanism culminating towards the SSW in a continental disruption behind the magmatic arc. The observed age progression of volcanism may be the result of the variations of the physical characteristics of the subduction. The spreading and thermal effect of the KAT plume may have an additional effect and also could account for the unusually large volume of magma. (Résumé d'auteur)